The petrology of the Gamsberg zinc deposit and the Bushmanland iron formations with special reference to their relationships and genesis - Rozendaal, A.(Abraham) (Stellenbosch : Stellenbosch University, 2012)
Folded maps in end-pocket of v. 2.